Solubilidade e resistência ao reparo de cimentos de ionômero de vidro submetidos a desafios ácidos - Mestrener, Leandro Rahal [UNESP] (2014)
The aim of this study was to evaluate the solubility of glass ionomer cements (GICs) immersed in acid solutions and subjected to brushing. In addition to assess the resistance to repair of GICs immersed in acidic solutions. Thirty specimens were prepared for each GICs (Vitreme, Vitro Fil LC, Vitro Fil, Maxxion R), with dimensions of 10mm in diameter and 3mm in height. After weighing they were divided into three groups and immersed in distilled water for 15 days (control group), hydrochloric acid for 2 hours (similar gastric juice) and Coca Cola for 15 days at 37 ° C. After immersion in the solutions, all test samples were subjected to repeated cycles of brushing. Then the specimens were embedded in acrylic resin letting up the entire surface exposed. After the surface treatment, a cylinder of the same cement was made in each specimen to evaluate the repair resistance, by the shear test. The storage was performed in the previously solutions for 7 days at 37° C with the exception that the hydrochloric acid solution was during 2 hours. The results were evaluated by analysis of variance and Fisher's test. The significance level was 5%. In relation to the solubility, resin modified GICs suffered only the action of hydrochloric acid, conventional GICs suffered action of the two acid solutions. For the repair test, it was found that only the GIC Vitro Fil LC showed statistically difference between the immersions used. It can be concluded that the hydrochloric acid has degradative action on all cements studied, but they had the ability to repair even over action of acid solutions excepcet for Vitro Fil LC, however it presented the best results for repair strenght